ESTIMATING INCIDENT SOLAR RADIATION IN TROPICAL ISLANDS WITH SHORT TERM WEATHER DATA - Sisuru Sendanayake; Nandika. P. Miguntanna; M.T.R Jayasinghe (European Scientific Journal, ESJ, 2014)
Solar radiation incident on a particular location depends on geographical and meteorological factors and as such vary spatially as well as temporally. For any given solar radiation related application an accurate prediction of incident solar radiation is important. However due to high cost of measuring and recording, solar radiation data are confined generally to a few locations, for example in Sri Lanka it is confined only to the capital city, Colombo. As such, a correlation to predict incident solar radiation based on meteorological and geographical parameters will have to be identified and validated taking into account the climatic differences in tropical regions with localized variations. In addition, due to non-availability of accurate historical meteorological data, estimated percentage variations are identified which can be used to predict incident solar radiation at a given location when two broad climatic regions are defined.